2006
DOI: 10.1088/0264-9381/23/12/012
|View full text |Cite
|
Sign up to set email alerts
|

Curvature-driven acceleration: a utopia or a reality?

Abstract: The present work shows that a combination of nonlinear contributions from the Ricci curvature in Einstein field equations can drive a late time acceleration of expansion of the universe. The transit from the decelerated to the accelerated phase of expansion takes place smoothly without having to resort to a study of asymptotic behaviour. This result emphasizes the need for thorough and critical examination of models with nonlinear contribution from the curvature.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 33 publications
0
50
0
Order By: Relevance
“…It is evident from the the generalised field equations(5-6) that the expressions between the curly brackets for ρ and p are similar to the analogous 4D FRW equations. Therefore the 4D energy density ρ 4 and the pressure P may be identified with the quantities (ρ−ρ 0 ) and (p−p 0 ) where ρ 0 and p 0 respectively denote the terms containing the higher dimensional coefficients in equations (5)(6). This, according to Mohammedi, is the usual and standard interpretation of higher dimensional equations of motion.…”
Section: Mohammedi's Workmentioning
confidence: 99%
“…It is evident from the the generalised field equations(5-6) that the expressions between the curly brackets for ρ and p are similar to the analogous 4D FRW equations. Therefore the 4D energy density ρ 4 and the pressure P may be identified with the quantities (ρ−ρ 0 ) and (p−p 0 ) where ρ 0 and p 0 respectively denote the terms containing the higher dimensional coefficients in equations (5)(6). This, according to Mohammedi, is the usual and standard interpretation of higher dimensional equations of motion.…”
Section: Mohammedi's Workmentioning
confidence: 99%
“…Das, Banerjee and Dadhich (Das, Banerjee and Dadhich 2006) indeed discussed models that show such a smooth transition analytically, but the models do not contain matter. However, it has been shown that, along with a matter field, any such model could behave in quite a different manner Amendola, Gannouji, Polarski and Tsujikawa 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Obviously the other option is to look for the modification of GR which allows the cosmic acceleration without introducing any exotic component. Scalar-tensor theories (Bertolami & Martins 2000;Banerjee & Paovn 2001a,b;Sen & Sen 2001;Mota & Barrow 2004a,b;Das & Banerjee 2008), f (R) gravity theory (Capozziello et al 2003;Carroll et al 2004;Vollick 2003;Nojiri & Odintsov 2003;Carroll et al 2005;Mena et al 2006;Nojiri & Odintsov 2006;Das et al 2006;Nojiri & Odintsov 2007a,b, 2009), different higher dimensional gravity theories (Deffayet et al 2002 Though different theoretical approaches are there to explain the phenomenon of cosmic acceleration, till now none of them is definitely known as the appropriate one. The present trend of modelling of late time cosmic acceleration is called reconstruction where the model is built up by taking the observational data directly into account.…”
Section: Introductionmentioning
confidence: 99%